THE EFFECT OF COMMITMENT, TRUST, RELATIVE DEPENDENCE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT PT PUPUK KALTIM BONTANG - Irma Meliaki Simamora; Maya Arianti (RADJA PUBLIKA, 2025)
This research is to find out how much pThe influence of commitment, trust, relative dependence on customer loyalty through customer satisfaction. Research methodsThe author will review the characteristics of research that include types of research, variables, data collection instruments, research implementation steps, population and samples, data collection and sources, validity and reliability of data, and data analysis techniques and hypothesis testing. This type of research is descriptive and causal research. Research resultsDescriptive analysis is used to determine the perception of 123 respondents regarding Commitment, Trust, and Relative Dependence, and to analyze its influence on Customer Loyalty through Customer Satisfaction at PT. Pupuk Kaltim Bontang. The test results show that the relationship betweencommitmenton customer satisfaction produces a t-count value that is greater than the t-table value (4,874> 1.65) and a significance value that is smaller than the level of accuracy (0.000 < 0.05) so that H0 is rejected. Then it has a path coefficient of 0.483. Thus, it can be concluded that there is a positive and significant influence of commitment on customer satisfaction.The average percentage value of respondents' assessment of the customer loyalty variable is included in the good category, on the continuum line, so it can be concluded that in this case it means that PT. Pupuk Kaltim Bontang has been able to improve its products and services so that PT. Pupuk Kaltim Bontang is a good business partner and can bring many benefits and opportunities for the growth and success of its customers' businesses.